Sum of 1 . 3 . 5 1 + 3 . 5 . 7 1 + 5 . 7 . 9 1 + . . u p t o ∞
This section requires Javascript.
You are seeing this because something didn't load right. We suggest you, (a) try
refreshing the page, (b) enabling javascript if it is disabled on your browser and,
finally, (c)
loading the
non-javascript version of this page
. We're sorry about the hassle.
Clearly, we can see that the n t h term is given by the pattern:
a n = ( 2 n − 1 ) ( 2 n + 1 ) ( 2 n + 3 ) 1
We need to calculate
∑ n = 1 ∞ a n ⇒ ∑ n = 1 ∞ ( 2 n − 1 ) ( 2 n + 1 ) ( 2 n + 3 ) 1
Since, there is no absolute pattern for such terms, so we need to simplify this sum onto simpler ones, and calculate them.
Now, by expanding 2 terms out of the three terms alternatively, we can see that:
( 2 n − 1 ) ( 2 n + 1 ) = 4 n 2 − 1 ( 2 n + 1 ) ( 2 n + 3 ) = 4 n 2 + 8 n + 3 ( 2 n − 1 ) ( 2 n + 3 ) = 4 n 2 + 4 n − 3
So, the required sum can be written as,
∑ n = 1 ∞ 8 1 ( 2 n − 1 ) ( 2 n + 1 ) ( 2 n + 3 ) ( 2 n + 1 ) ( 2 n + 3 ) + ( 2 n − 1 ) ( 2 n + 1 ) − 2 ( 2 n − 1 ) ( 2 n + 3 ) ⇒ 8 1 ∑ n = 1 ∞ ( 2 n − 1 ) ( 2 n + 1 ) ( 2 n + 3 ) ( 2 n + 1 ) ( 2 n + 3 ) + ( 2 n − 1 ) ( 2 n + 1 ) ( 2 n + 3 ) ( 2 n − 1 ) ( 2 n + 1 ) − ( 2 n − 1 ) ( 2 n + 1 ) ( 2 n + 3 ) 2 ( 2 n − 1 ) ( 2 n + 3 ) ⇒ 8 1 ∑ n = 1 ∞ ( 2 n − 1 ) 1 + ( 2 n + 3 ) 1 − ( 2 n + 1 ) 2
Now, by inserting the first few values, we can see the pattern, i.e,
= 8 1 [ ( 1 + 5 1 − 3 2 ) + ( 3 1 + 7 1 − 5 2 ) + ( 5 1 + 9 1 − 7 2 ) + ( 7 1 + 1 1 1 − 9 2 ) + ( 9 1 + . . . ]
Now, looking at the pattern, we can see that some all terms get cancelled, and the ones in the end will tend to xero, So, we are left with,
= 8 1 ( 1 − 3 2 + 3 1 ) = 8 1 × 3 2 = 1 2 1 = 0 . 0 8 3 3
CHEERS!:)
Problem Loading...
Note Loading...
Set Loading...
Note that n ( n + 2 ) ( n + 4 ) 1 = 4 1 ( n ( n + 2 ) 1 − ( n + 2 ) ( n + 4 ) 1 ) Substituting n = 1 , 3 , 5 , . . . , we find that it is a telescoping sum. All terms other than the first, 4 1 ( 1 ( 1 + 2 ) 1 ) = 1 2 1 cancel out. Thus 1 2 1 = 0 . 0 8 3 3 3 . . . is the answer.